Sanguinarine Regulates Tumor-Associated Macrophages to Prevent Lung Cancer Angiogenesis Through the WNT/β-Catenin Pathway - Cui, Yajing; Luo, Yingbin; Qian, Qiaohong; Tian, Jianhui; Fang, Zhihong; Wang, Xi; Zeng, Yaoying; Wu, Jianchun; Li, Yan (Frontiers in Oncology, 2022)
Tumor-associated macrophage (TAM)-mediated angiogenesis in the tumor microenvironment is a prerequisite for lung cancer growth and metastasis. Therefore, targeting TAMs, which block angiogenesis, is expected to be a breakthrough in controlling the growth and metastasis of lung cancer. In this study, we found that sanguinarine (SANG) inhibits tumor growth and tumor angiogenesis of subcutaneously transplanted tumors in Lewis lung cancer mice. Furthermore, sanguinarine inhibited the proliferation, migration, and lumen formation of HUVECs and the expression of CD31 and VEGF by regulating the polarization of M2 macrophages in vitro. However, the inhibitory effect of sanguinarine on angiogenesis remained in vivo despite the clearance of macrophages using small molecule drugs. Further high-throughput sequencing suggested that Wnt/β-catenin signaling might represent the underlying mechanism of the beneficial effects of sanguinarine. Finally, the β-catenin activator SKL2001 antagonized the effect of sanguinarine, indicating that sanguinarine can regulate M2-mediated angiogenesis through the Wnt/β-catenin pathway. In conclusion, this study presents the first findings that sanguinarine can function as a novel β-catenin inhibitor to regulate the polarization of M2 macrophages and inhibit angiogenesis, which has potential application value in immunotherapy and antiangiogenic therapy for lung cancer.